The Lion, the Witch and the Wardrobe : The Chronicles of Narnia - "Lewis, C.S" (Harper collins Publishers: india, 2012)
NARNIA...the land beyond the wardrobe, the secret country known only to Peter, Susan, Edmund, and Lucy...the place where the adventure begins. Lucy is the first to find the secret of the wardrobe in the professor's mysterious old house. At first, no one believes her when she tells of her adventures in the land of Narnia. Soon, Edmund, Peter, and Susan discover the magic and meet Aslan, the Great Lion, for themselves. In the blink of an eye, their lives are changed forever.
Keywords: English-Fiction